2018
DOI: 10.3847/1538-4357/aac7c7
|View full text |Cite
|
Sign up to set email alerts
|

Possible Association of Two Stellar Bowshocks with Unidentified Fermi Sources

Abstract: The bowshocks of runaway stars had been theoretically proposed as gamma-ray sources. However, this hypothesis has not been confirmed by observations up to date. In this paper, we present two runaway stars (λ Cep and LS 2355) whose bowshocks are coincident with the unidentified Fermi gamma-ray sources 3FLG J2210.1+5925 and 3FGL J1128.7-6232, respectively. After performing a cross-correlation between different catalogues at distinct wavelengths, we found that these bowshocks are the most peculiar objects in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…While cyclotron radiation is emitted at very low and ultra-low frequencies, far below the spectral range of observational instruments, the bremsstrahlung spectrum reaches frequencies in the extreme ultraviolet and soft X-ray regime. Higher thermal speeds of electrons would result in even higher frequencies, as were observed by Sánchez-Ayaso et al (2018), for example.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…While cyclotron radiation is emitted at very low and ultra-low frequencies, far below the spectral range of observational instruments, the bremsstrahlung spectrum reaches frequencies in the extreme ultraviolet and soft X-ray regime. Higher thermal speeds of electrons would result in even higher frequencies, as were observed by Sánchez-Ayaso et al (2018), for example.…”
Section: Discussionmentioning
confidence: 72%
“…The resulting models have been successfully compared to observational images and data in various observables (e.g. Kobulnicky et al 2017;Sánchez-Ayaso et al 2018, and references therein). The shapes of these structures strongly depend on the physical parameters of the star and on the surrounding interstellar medium (ISM) (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…No associated emission was found, but from the resulting upper limits a constraint on the very high energy emission was obtained: it should be less than 0.1 to 1% of the kinetic wind energy. Recently, Sánchez-Ayaso et al (2018) presented two runaway stars (Lambda Cephei and LS 2355) whose bow shocks are coincident with two unidentified Fermi gamma-ray sources from the third Fermi 3FGL catalog (Acero et al 2015). After cross-correlation between different catalogs at distinct wavelengths, the authors found that these bow shocks are the most peculiar objects in the Fermi position ellipses.…”
Section: Introductionmentioning
confidence: 99%
“…E. S. S. Collaboration et al 2018) emission from stellar BSs. The only exception is the possible association of two stellar BSs with Fermi sources (Sánchez-Ayaso et al 2018). Moreover, nonthermal radio emission from other BSs also remains elusive (C.S.…”
Section: Introductionmentioning
confidence: 99%